Rancang Bangun Sistem Monitoring Pengolahan Limbah Cair Tahu Di Kabupaten Purbalingga Berbasis Internet of Things - Garichwan Fathurrahman Arafat; Aditya Wijayanto; Novian Adi Prasetyo (STMIK Budi Darma, 2022)
In the production of tofu, it usually produces liquid waste which can cause environmental pollution when no processing is carried out which will have an impact on local residents. Disposal of liquid waste from the production of tofu without going through processing will result in air pollution in the form of a pungent odor and too low oxygen and pollution in the water which will become dirty. Liquid waste generated from the production of tofu contains organic substances that cause microbial growth in the water which results in decreased oxygen levels in the water and the water becomes cloudy. Based on these problems, a monitoring system for turbidity and acid-base levels of the tofu industrial wastewater in Purbalingga Regency based on the Internet of Things was designed by utilizing the NodeMCU ESP8266 which is connected to a Turbidity sensor, pH sensor, DS18B20 sensor, LCD 16x2 I2C, relay, and a water pump that will connected to the Telegram Bot for monitoring and control. Telegram bots can work when Telegram and the network are turned on and connected to the internet. From the results of testing the system produces tools that are in accordance with what the author expects. All sensors and relays can work well on the waste onjek, the water pump also works well so that it can carry out waste disposal when the turbidity level has reached less than 35 which is carried out after the decomposition process is complete. The system can also send notifications to the Telegram Bot when the pump is on and when commands are requested via the gadget, resulting in the conclusion that the system works in real time and must be connected to the internet network.